The effect of simultaneous refinement and modification by cerium on microstructure and mechanical properties of Al-8% Si alloy. (1st November 2016) - Vijayan, Vijeesh; Prabhu, K. Narayan
Abstract : The effect of cerium melt treatment on microstructure and mechanical properties of gravity die cast Al-8% Si alloy was studied. The addition of Ce transformed the large columnar α-Al grains into fine equiaxed grains and modified the acicular eutectic Si into fine fibrous form. The addition of Ce resulted in the formation of needle-shaped complex Ce intermetallic along the grain boundaries. Electrical conductivity measurements are used for the first time to reveal the effect of Ce addition on modification of the eutectic Si. The electrical conductivity of the alloy increased with Ce melt treatment. Scanning Electron Microscopy results suggests that the Ce particles did not heterogeneously nucleate the α-Al grains, instead the fine equiaxed grains were formed through an invariant reaction between the liquid melt and Ce phase. The ultimate tensile strength, % elongation and hardness of the alloy significantly improved due to simultaneous modification and refinement.